Analisis dan Identifikasi Ketersediaan Ruang Terbuka Hijau (RTH) Non Alami di Perkotaan Kabupaten/Kota - Armijon Armijon (Rekayasa : Jurnal Ilmiah Fakultas Teknik Universitas Lampung, 2019)
an important part in the planning, development and management of built-up areas (cultivation area) and natural areas in urban areas. RTH management can be improved if communication between stakeholders is more intensive and gets holistic information and can be continuously updated. Based on this, it is necessary to identify an availability of public RTH in the city which is expected to be able to materialize the urban space; safe, comfortable, productive and sustainable. In this study an analysis and identification of the availability of RTH is non-natural in urban areas was carried out, specifically for the capital city (regency/city) in Lampung province to realize more quality, beautiful, comfortable, healthy and sustainable urban spaces through increasing the quality and quantity of RTH. This research includes studies methodology and approach to conducting research, methods of data collection, data processing and analysis, including literature review and theoretical studies and similar case studies, problem solving analysis, preparation of development concepts. The next stage is using Remote Sensing technology and Geographic Information System (GIS) Analysis to produce; Availability Analysis, Area Identification, and directions for RTH priority locations in Lampung province. Research activities in the urban area of Lampung province resulted in the identification of 18 points potential RTH in the capital centers (regency/city) in the Lampung province and selected 2 points priority RTH locations (main development).